All Trans Retinoic Acid Regulates Expression of Genes Invoved in Cell Senescence Pathway in Gastric Cancer Cell Line MKN45 - Binh, Luu Thi; Huong, Le Thi Thanh; Thanh, Nguyen Trung; Hung, Nguyen Phu (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4DO - 10.25073/2588-1140/vnunst.4907, 2019)
Cellular senescence is a state in wich cells can not longer divide. The dysregulation of the cell senescence signaling pathway could lead to uncontrolled cell proliferation and formation of malignant cells. Intervening in cell senessence signaling pathway to bring cancer cells back to cell senessence state is a potential way in cancertreatment. Recent studies show that tumor cells can undergo celluar senessencestate by using special chemotherapy. In this study, we indicatedthat All trans retinoic acid (ATRA) is able to influence the expression of genes involved in cell senessence signaling pathway in gastric cancer cells MKN45. ATRA down-regulatesthe expression of important genes controlling cell growth. On the other hand, ATRA up-regulate the expression of GADD45A, P21 and P53 genes that play an important role in the signaling pathway of cells.This finding suggestes that ATRA could inhibite MKN45 cells through activating cell senescence signaling pathway. Keywords: All trans retinoic acid, gastric cancer stem cell, cell senescence. References [1] L. Hayflick, P.S. Moorhead, The serial cultivation of human diploid cell strains, Exp. Cell Res. 25 (1961) 585-621. https://doi.org/10.1016/0014-4827 (61)90192-6. [2] V. Dupé, N.B.Ghyselinck, V. Thomazy, L. Nagy, P.J. Davies, P. Chambon and M. Mark, Essential roles of retinoic acid signaling in interdigital apoptosis and control of BMP-7 expression in mouse autopods, Development Biology. 208 (1999) 30-34. https://doi.org/10.1006/dbio.1998. 9176. [3] López-Otín Carlos, et al, The hallmarks of aging, Cell. 153 (2013) 1194-1217. https://doi.org/ 10.1016/j.cell.2013.05.039. [4] Kuilman Thomas, et al, The essence of senescence, Genes & development. 24 (2010) 2463-2479. https://doi.org/10.1101/gad.1971610. [5] Collado Manuel and Manuel Serrano, Senescence in tumours: vidence from mice and humans, Nature Reviews Cancer. 10 (2010) 51-57. https:// doi.org/10.1038/nrc2772. [6] Hofmann, L. Sandra, Retinoids:"differentiation" agents for cancer treatment and prevention, Am J Med Sci. 304 (1992) 202-213. https://doi.org/10. 1097/00000441-199209000-00010. [7] Heo Shin-Hee, Juri Kwak and Kyung Lib Jang, All-trans retinoic acid induces p53-depenent apoptosis in human hepatocytes by activating p14 expression via promoter hypomethylation, Cancer letters. 362 (2015) 139-148 https://doi.org/10. 1016/j.canlet.2015.03.036. [8] P.H. Nguyen, J. Giraud, C. Staedel, L. Chambonnier, P. Dubus, E. Chevret, H. Bœuf, X. Gauthereau X, Rousseau B, Fevre M, Soubeyran I, Belleannée, S. Evrard, D. Collet, F. Mégraud, C. Varon, Knudsen, S. Erik, All-trans retinoic acid targets gastric cancer stem cells and inhibits patient-derived gastric carcinoma tumor growth, Oncogene. 35 (2016) 5619-5628. https://doi.org 10.1038/onc.2016. 87. [9] SherrCharles, Frank McCormick, The RB and p53 pathways in cancer, Cancer cell. 2(2002) 103-112. https://doi.org/10.1016/S1535-6108(02)00102-2. [10] Ngo Thu Ha, Luu Thi Binh, Le Thi Thanh Huong, Mai Van Linh, Nguyen Đac Trung, Nguyen Phu Hung, All-trans Retinoic Acid Effect on the Apoptosis Gene Expression of Gastric Cancer Cell (in Vietnamese), Journal of Sciences. 33 (2017) 138-143. https://doi.org/10.25073/2588-1140/vnunst. 4540. [11] K.J. Livak, T.D. Schmittgen, Analysis of relative gene expression data using real-time quantitative PCR and the 2(-Delta Delta C(T)) Method, Method. 25 (2001) 402-408. https://doi.org/10. 1006/meth.2001.1262. [12] E.Nelson Brown., Rinath Jeselsohn., Teeru Bihani., Miaofen G. Hu., Parthena Foltopoulou.,Charlotte Kuperwasser and Philip W. Hinds, Cyclin D1 activity regulates autophagy and senescence in the mammary epithelium,Cancer Res. 72 (2012) 6477-6489. https://doi.org/10.1158/0008-5472.CAN-11-4139. [13] M. Trimarchi Jeffrey, Jacqueline A. Lees, Sibling rivalry in the E2F family, Nat Rev Mol Cell Biol. 3 (2002) 11-12. https://doi.org/10.1038/ nrm714. [14] Stevaux Olivier, Nicholas J. Dyson, A revised picture of the E2F transcriptional network and RB function, Current opinion in cell biology. 14 (2002) 684-691. https://doi.org/10.1016/S0955-0674(02)00388-5. [15] Wu Kou-Juey, Muh-Hwa Yang, Epithelial-mesenchymal transition and cancer stemness: the Twist1-Bmi1connection, Bioscience reports. 31 (2011) 449-455. https://doi.org/10.1042/BSR20 100114. [16] J.J.L. Jacobs, K. Kieboom, S. Marino, R.A. DePinho, M. van Lohuizen, The oncogene and Polycomb-group gene bmi-1 regulates cell proliferation and senescence through the ink4a locus, Nature. 397(1999) 164-168. https://doi.org/ 10.1038/16476 [17] R. Maestro, A.P. Dei Tos, Y. Hamamori, S. Krasnokutsky, V. Sartorelli, L. Kedes, D.H. Beach,G.J. Hannon,Twist is a potential oncogene that inhibits apoptosis, Genes Dev. 13 (1999) 2207-2217. https://doi.org/10.1101/gad.13.17.2207 [18] Qian Yingjuan, Xinbin Chen, Senescence regulation by the p53 protein family,Methods Mol Biol. 965 (2013) 37-61. https://doi.org/10.1007/ 978-1-62703-239-1_3 [19] A. Karimian, Y. Ahmadi, B. Yousefi, Multiple functions of p21 in cell cycle, apoptosis and transcriptional regulation after DNA damage, DNA Repair (Amst). 42 (2016) 63-71. https://doi. org/10.1016/j.dnarep.2016.04.008 [20] Y. Xiong,G.J. Hannon, H. Zhang, D. Casso, R. Kobayashi, D. Beach,P21 is a universal inhibitor of cyclin kinases, Nature. 366 (1993) 701-704. https://doi.org/10.1038/366701a0 [21] L. Fang, M. Igarashi, J. Leung, M.M. Sugrue, S.W. Lee, S.A. Aaronson, p21Waf1/Cip1/Sdi1 induces permanent growth arrest with markers of replicative senescence in human tumor cells lacking functional p53, Oncogene. 18 (1999) 2789-2797. https://doi.org/10.1038/sj.onc.1202615 [22] G. Jackson James, M. OliviaPereira-Smith, p53 is preferentially recruited to the promoters of growth arrest genes p21 and GADD45 during replicative senescence of normal human fibroblasts,Cancer Research. 66 (2006) 8356-8360. https://doi.org/10. 1158/0008-5472.can-06-1752.